2019
DOI: 10.1093/labmed/lmz034
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Resolution Melting PCR to Detect the Genomic Fungal ITS 2 Region

Abstract: Background Invasive fungal infections (IFIs) are a main cause of morbidity and mortality. High-resolution melting polymerase chain reaction (HRM PCR) is promising for the identification of fungal species via the detection of internal transcribed spacer 2 (ITS2). Objectives To assess the sensitivity and specificity of HRM PCR in diagnosing IFIs, compared with blood culture. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Similar to our results, Lau et al (17) showed that the RT-PCR had a higher sensitivity for detecting IFIs than blood culture tests. In contrast, Nawar et al (18) reported that HRM-PCR had a lower sensitivity for detecting IFIs than the blood culture technique.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to our results, Lau et al (17) showed that the RT-PCR had a higher sensitivity for detecting IFIs than blood culture tests. In contrast, Nawar et al (18) reported that HRM-PCR had a lower sensitivity for detecting IFIs than the blood culture technique.…”
Section: Discussionmentioning
confidence: 94%
“…Günümüzde bazı araştırmacılar Candida türlerinin belirlenmesinde RT-PCR HRMA yöntemini tercih etmektedir (32,34,38,39) . Nemcova ve ark.…”
Section: Candida Parapsilosis -13 13unclassified